Effects of selenomethionine on intestinal microbiota and its metabolism in mice infected with porcine deltacoronavirus - Li, Haiyan; Shi, Yaya; Zhang, Tongjun (Frontiers in Microbiology, 2025)
IntroductionPorcine deltacoronavirus (PDCoV) is a novel enteropathogenic porcine coronavirus that primarily affects the intestinal tract. Modulating the intestinal microbiota could alleviate clinical signs and maintain the physical and chemical barrier of the intestines in piglets infected with PDCoV. Our previous study showed that selenomethionine (SeMet) could attenuate intestinal damage in PDCoV-infected piglets or mice. However, its influence on gut microbiota and metabolites is still unclear. We aimed to investigate the effect of SeMet on gut microbiota and metabolites in PDCoV-infected mice.MethodsIn this study, samples of the contents of the colon were collected from mice in the Control group, the PDCoV group, and the SeMet+PDCoV group (0.3 mg/kg Se). These samples were analyzed using 16S rRNA sequencing, metabolomics analysis, and bioinformatics software to investigate the correlation between the gut microbiota and metabolites.ResultsThis study suggested that PDCoV infection could induce disorder in the intestinal microbiota of mice. SeMet treatment was found to restore the balance of this microbiota, including the bacteria Lactobacillus and Bifidobacterium. Altered intestinal microbiota also affect gut metabolism. Supplementing with SeMet brought the metabolites of the intestinal microbiota of PDCoV-infected mice closer to those of the Control group. These metabolites included phenylalanine-proline, tyrosine-proline, tyrosine, tryptophan, glutamate and octadecanamide. This contributed to an improved antiviral infection and immune response. Correlation analysis revealed a strong correlation between the gut microbiota and its metabolites.ConclusionThe alleviating effect of SeMet on intestinal damage caused by porcine delta coronavirus may be related to the intestinal microbiota and its metabolites.